A Field Test of Opportunities for Teen Dating Violence Disclosure in School-Based Relationship Education Programs - Kan, Marni L. (Journal of interpersonal violence, 2022)
School-based relationship education programs offer an opportunity to identify youth who are experiencing teen dating violence (TDV), support their safety, and connect them with individualized services or referrals. However, no research has tested the feasibility or accuracy of approaches to create opportunities for TDV disclosure in the context of school-based programs. The current study presents the results of a field test comparing three tools used to provide opportunities for TDV disclosure (two questionnaire-style tools and one universal education discussion guide). High school students from two federally funded healthy marriage and relationship education (HMRE) program sites (N = 648) were offered the three tools in random order over the course of the HMRE program, which lasted between 3 weeks and 3 months and took place during the school day. Onsite qualitative interviews with HMRE program staff and their local domestic violence program partners assessed how service providers saw the tools and the process of implementing them. Latent class models examined the accuracy of the tools in identifying TDV. Sensitivities of the tools were low and specificities were high; the questionnaire-style tools tended to have higher sensitivities and fewer classification errors than the universal education tool. Several three-item combinations from across the tools performed better than any intact tool, suggesting that shorter assessments may be effective, provided they include items on sexual coercion and physical violence. Qualitative findings suggested that implementation of TDV assessment and universal education in school settings is a viable strategy, provided programs are able to gain support from school staff, adapt to tight time constraints, and plan procedures for protecting student privacy and confidentiality.